A comparative study on the ballistic performance of high nitrogen steel and rolled homogeneous armour steel against 7.62 mm ball and 12.7 mm armour piercing projectiles. (2021) - Bhav Singh, B.; Sukumar, G.; Sivakumar, K.; Madhu, V.; Arockia Kumar, R.
Abstract: Ballistic performance of high-nitrogen steel (HNS) plates and RHA steel plates were evaluated against 7.62 mm ball and 12.7 mm armour piercing (AP) projectiles The impact velocities of 7.62 mm ball and 12.7 mm armour-piercing projectiles were 850 ± 10 m/s and 840 ± 10 m/s respectively. Critical thickness at which projectile is stopped was found from ballistic tests on different thickness targets and it was used for comparing the ballistic performance. HNS plates showed improved impact resistance (in terms of minimum areal density at which projectile is stopped) than that of RHA steel plates against both 7.62 ball and 12.7 mm armour piercing projectiles. Improved impact resistance of HNS plates could be correlated with its superior high strain rate flow stress values with respect to RHA steel. Microstructural evaluation revealed that adiabatic shear band induced plugging and ductile-hole growth are the major failure modes in both targets against 7.62 ball and 12.7 AP projectiles respectively.